PENGARUH KUALITAS PRODUK, PELAYANAN, HARGA DAN LOKASI TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Konsumen Rumah Makan Super Geprek Dinoyo Malang) - Rismatul Karomah; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The aim of this study was to know the effect of product quality, service, price and location about customer loyalty through satisfaction as an intervening variable to Super Geprek Restaurant at Dinoyo Malang.The research design in this study was quantitative. approach in the form of explanatory research. The population was all consumers who became unknown customers at “Super Geprek” Restaurant. The sampling technique that used was an accidental sampling. Analysis method which used multiple linear regressions. So it could be determined as follows: 1) Satisfaction was an intervening variable that had a relationship between product quality and loyalty, 2) satisfaction was an intervening variable that had a relationship between service quality and loyalty, 3) satisfaction was an intervening variable that had a relationship between price and loyalty, 4) satisfaction was an intervening variable that had a relationship between location and loyalty. Keywords: Product Quality, Service Quality, Price, Satisfaction And Loyalty.